Mite (Arachnida: Acari) diversity and abundance on oil palms in the central region of the Brazilian Amazonia - Da Cruz, Wilton Pires [UNESP]; Krug, Cristiane; Nascimento De Vasconcelos, Geraldo Jose; De Moraes, Gilberto Jose (Systematic & Applied Acarology Soc London, Natural History Museum, 2019)
The African oil palm, Elaeis guineensis Jacq., is the second oil producing plant most extensively cultivated worldwide. The American oil palm, Elaeis oleifera (Kunth) Cortes, is a similar species rarely planted for commercial oil production, but often used for the production of hybrids with the African oil palm. The objective of this work was to compare the mite fauna of different genotypes of the African and the American oil palms as well as of their hybrids. In total, three and five genotypes of the African and the American oil palms and two of their hybrids available at an experiment station in the central part of the Brazilian Amazonia (Campo Experimental Rio Urubu, Embrapa Amazonia Ocidental, Rio Preto da Eva, Amazonas State) were evaluated. Samples were collected in the wet (May 2012) and the dry (October, November 2013) seasons. On American oil palms, mite density was much higher in the wet than in the dry season, while on palms of other groups no significant differences were observed between seasons. Phytophagous mites corresponded to 91.1% of all mites found and Eriophyoidea was by far the most abundant group of these mites. Plant damage by this and other mite groups was not noticed. Mites of the family Tenuipalpidae, to which Raoiella indica Hirst belongs, were not found in this study. In previous studies, R. indica was reported to cause severe damage to several plant species. Phytoseiid species richness and diversities were also higher in the American oil palms than on palms of other groups. The phytoseiids Amblyseius perditus Chant & Baker and Iphiseiodes kamahorae De Leon were the most abundant predators, the first almost exclusively on BR 174 and Coari, and the second, on Manicore genotypes of the American oil palms. Phytoseiid diversity on hybrids was as low as on African oil palm genotypes in the dry season and lower than on other palm groups in the wet season.
Keywords: Biodiversity; Biological control; Ecology; Phytophagous mites; Phytoseidae; Raoiella indica